Characterization of Ground Thermal Conditions for Shallow Geothermal Exploitation in the Central North China Plain (NCP) Area - Wanli Wang; Guiling Wang; Feng Liu; Chunlei Liu (Energies, 2022)
The central North China Plain (NCP) is one of the rapidly developing regions in China which has a great potential for ground source heat pump (GSHP) system applications. However, the ground thermal property, which is a prerequisite for GSHP system design, has been insufficiently investigated. In this paper, the ground thermal conditions including ground temperature and thermal conductivity are characterized in three representative hydrogeological regions in the NCP area: the piedmont alluvial plain, the central alluvial plain, and the coastal plain. Results show that the geothermal gradient below 40 m in depth in this area ranges from 0.018 °C/m to 0.029 °C/m. Although the thermal conductivity measured by soil samples differs slightly among the three regions, parameters in the piedmont plain have a larger variability than in the central and coastal plain due to the significant heterogeneity of the lithology. Thermal conductivity measured by the thermal response test (TRT) ranges between 2.37 and 2.68 W/(m·K) in the piedmont plain and varies between 1.35 and 1.94 W/(m·K) in the central and coastal plain, indicating that the piedmont plain has a higher potential for shallow geothermal exploitation than other two sub-areas. Comparing the TRT with laboratory measurements, the thermal conductivity obtained by the TRT is greater than that of the lab measurements in the piedmont plain due to the TRT outputs including the effects of groundwater flow. Therefore, the TRT is highly recommended to estimate the effective thermal conductivity of the ground in the piedmont plain, while laboratory and field tests are both suitable methods for the determination of thermal conductivity in the central and coastal plains.